PENYERAPAN TENAGA KERJA PADA INDUSTRI KACANG DI KABUPATEN PATI TAHUN 2006-2010 - Retnonigsih, Dwi (Geo-Image, 2013)
Peanut industry is an important sector in the field of processing industry enterprises in Pati regency. This study uses a stratified proportional random sampling technique. Samples taken from four groups in peanut industry are 116 people. The results showed the fluctuation rate of labor absorption peanut industry between 2006 and 2010. Based on the demographic characteristics, the average workers female age 35 years and comes from the District of Pati. Based on the social characteristics, the education beckground of the are primary education. Based on the economic characteristics , the workers household has income per month Rp.1.890.000, 00 Rp.1.280.000 with family expenses, 00. Peanut industry locations in 18 villages of 7 districts. The raw material for the domestic industry comes from the district, from inter-district for small industries, and from other provinces and countries for big industry. The marketing of the product of household and small industry only reach the district, while the big industry is able to export to other countries.